THE THE ROLE OF NUTRITIONAL STATUS ON HEMOGLOBIN LEVELS IN ADOLESCENTS - Kusbandiyah, Jiarti; Rahmawati, Wenny; Sulistyowati, Agus (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Adolescents were one of the strong foundations for the future of the nation because of their role in development and progress of the country. Healthy physical and psychological conditions will form a strong and resilient adolescent character which is affected by adequate nutritional intake. So that if nutrients are not sufficient, it can cause disturbances in metabolic processes. Inadequate intake of nutrients such as protein and iron will aggravate the occurrence of anemia and lead to malnutrition. Indirectly, nutritional status will also affect the occurrence of anemia. Objectives: This study was to examine the relationship between nutritional status and adolescent hemoglobin levels. Methods: This study was an analytic study with Cross Sectional approach. Respondents were 46 students of SMP PGRI 01 Bantur in Malang regency conducted in August 2023. Independent variable was nutritional status using weight, height and Body mass index (BMI) and dependent variable was anemia using hemoglobin level. BMI was calculated using formula weight divided by height square. The analysis used both univariate and bivariate analysis. Bivariate analyzed using Spearman rank correlation test. Results: Results showed 76,1% adolescents classified normal nutritional, 19,6% overweight and 2,2% underweight and obese. The hemoglobin level, 86,9% normal and 13,1% anemia. Based on the results of statistical tests using rank spearman test, the p value = 0.044 less than 0,05. It means there was a significant correlation between nutritional status and anemia. Conclusion: There is a relationship between nutritional status with Hb levels in adolescents. Enrichment of nutritional intake will give big impact on nutritional and anemia status among adolescents.